Effects of a Diet Rich in n‐3 Polyunsaturated Fatty Acids on Hepatic Lipogenesis and Beta‐Oxidation in Mice. Issue 5 (14th March 2014) - Bargut, Thereza C. Lonzetti; Frantz, Eliete D. C.; Mandarim‐de‐Lacerda, Carlos A.; Aguila, Marcia Barbosa
Abstract: Here, we investigate whether a diet rich in fish oil can lead to the development of hepatic alterations associated with non‐alcoholic fatty liver disease (NAFLD). To achieve this goal, we provided, for 8 weeks, four different diets to 3‐month‐old C57BL/6 mice: (a) standard‐chow diet (SC; 40 g soybean oil/kg diet, 10 % of the total energy content from lipids), (b) fish oil diet (FO; 4 g soybean oil and 36 g fish oil/kg diet, 10 % of the total energy content from lipids), (c) high‐fat diet (HF; 40 g soybean oil and 238 g lard/kg diet, 50 % of the total energy content from lipids), and (d) high‐fish oil diet (HFO; 40 g soybean oil and 238 g fish oil/kg diet, 50 % of the total energy content from lipids). Biochemical analyses, stereology, western‐blotting and RT‐qPCR were used. In the HF group, we found evidence of obesity, metabolic syndrome, and liver damage, along with hypertriglyceridemia, hepatic insulin resistance, and steatosis. On the other hand, the HFO group did not present these alterations and remained similar to the controls. The changes observed in the animals fed the HF diet were accompanied by an increase in hepatic lipogenesis and a decrease in beta‐oxidation; meanwhile, in the HFO group, the opposite results were found, that is, reduced lipogenesis and elevated beta‐oxidation, were most likely responsible for the prevention of deleterious hepatic alterations and liver damage. In conclusion, a diet rich in fish oil has beneficial effects on hepatic insulin resistance, lipogenesis and beta‐oxidation and prevents hepatic tissue from liver damage and NAFLD.